Indicadores de desempenho dos negócios: avaliação de sua importância no acompanhamento e revisão de ações estratégicas em empresas de manufatura (um estudo de caso) - Barbosa, Hamilton Correa (2008)
The thesis offers a contribution to understanding the structure that involves the system of indicators and their implications and connections, proposing a list of requirements for a definition of key indicators that give feedback and align with the strategic actions of the company, enabling the organization to do necessary adjustments to the company action plan. To check the implementation of the list, the thesis provides a case study in which the deviations can be seen in relation to the road map proposed by the list, and to what extent these deviations are related to the delay of the strategic actions of the company under study.